THE CONCEPT OF EDUCATOR CHARACTER: A THEO-LEGALISTIC STUDY BASED ON THE QUR'AN, HADITH, AND INDONESIAN NATIONAL EDUCATION LAW - DR. NURHASNAWATI; DR. SAWALUDDIN; ABD. HARIS (Hamdard Islamicus, 2025)
This article aims to describe the Conception of Educator Character in National Education from a Theo-Legalistic Approach based on the Holy Qur’an, Hadith, and the Law on the National Education System in Indonesia. This study is a library-based research. Library research involves collecting data from various literature sources. The primary data sources in this study are the Holy Qur’an, Hadith, and the Law on the National Education System in Indonesia. Data collection techniques include observation, documentation, and triangulation. Data analysis is conducted using content analysis, following the stages of data reduction, data presentation, and conclusion drawing. The results of this study indicate that the conception of educator character has been explained in the Holy Qur’an, Hadith, and Law No. 20 of 2003. For example, Surah Ar-Rahman (verses 1–4), Surah An-Najm (verses 5–6), and Surah An-Nahl (verses 43–44), along with several Hadiths, outline the characteristics that an educator must possess. Among the qualities highlighted are: embodying ar-raÍmÉn (compassion and mercy), sincerity in educating students, competence in public speaking, the ability to design optimal lesson plans, professional qualifications as an educator, readiness both physically and spiritually, being a source of knowledge for students, and understanding the duties, functions, and roles of an educator. Furthermore, according to various Hadiths, an educator should emulate the Prophet (Øal Allah-u-‘alaihe wa sallam) in teaching activities. This principle is also reflected in Law No. 20 of 2003 and is further elaborated in the Regulation of the Minister of National Education (Permendiknas) of 2010. Therefore, an educator who embodies these principles can effectively fulfill their role in national education.